Genetically predicted C-reactive protein mediates the association between rheumatoid arthritis and atlantoaxial subluxation - Yuan, Jiaqin; Xiong, Xiaoqin; Zhang, Bin; Feng, Qingyuan; Zhang, Jinglin; Wang, Wenting; Tang, Jia (Frontiers in Endocrinology, 2022)
Objective. Investigating the causal relationship between rheumatoid arthritis (RA) and atlantoaxial subluxation (AAS), and identifying and quantifying the role of C-reactive protein (CRP) as a potential mediator. Methods. Using summary-level data from a genome-wide association study (GWAS), a two-sample Mendelian randomization (MR) analysis of genetically predicted rheumatoid arthritis (14,361 cases, and 43,923 controls) and AAS (141 cases, 227,388 controls) was performed. Furthermore, we used two-step MR to quantitate the proportion of the effect of c-reactive protein-mediated RA on AAS. Results. MR analysis identified higher genetically predicted rheumatoid arthritis (primary MR analysis odds ratio (OR) 0.61/SD increase, 95% confidence interval (CI) 1.36-1.90) increased risk of AAS. There was no strong evidence that genetically predicted AAS had an effect on rheumatoid arthritis risk (OR 1.001, 95% CI 0.97-1.03). The proportion of genetically predicted rheumatoid arthritis mediated by C-reactive protein was 3.7% (95%CI 0.1%−7.3%). Conclusion. In conclusion, our study identified a causal relationship between RA and AAS, with a small proportion of the effect mediated by CRP, but a majority of the effect of RA on AAS remains unclear. Further research is needed on additional risk factors as potential mediators. In clinical practice, lesions of the upper cervical spine in RA patients need to be given more attention.